2006
DOI: 10.1042/bj20051427
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-ATPases in non-failing and failing heart: evidence for a novel cardiac sarco/endoplasmic reticulum Ca2+-ATPase 2 isoform (SERCA2c)

Abstract: We recently documented the expression of a novel human mRNA variant encoding a yet uncharacterized SERCA [SR (sarcoplasmic reticulum)/ER (endoplasmic reticulum) Ca2+-ATPase] protein, SERCA2c [Gélébart, Martin, Enouf and Papp (2003) Biochem. Biophys. Res. Commun. 303, 676-684]. In the present study, we have analysed the expression and functional characteristics of SERCA2c relative to SERCA2a and SERCA2b isoforms upon their stable heterologous expression in HEK-293 cells (human embryonic kidney 293 cells). All S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 45 publications
(78 reference statements)
4
71
0
2
Order By: Relevance
“…SERCA2b differs from SERCA2a by an extension of 46 amino acids that forms an additional trans-membrane domain setting the SERCA2b C terminus in the SR lumen [37]. Functional characterization of SERCA2 isoforms performed in transfected HEK-298 cells clearly indicated that the SERCA2a isoform displays a lower affinity for Ca 2+ (K0.5 = 0.985 µM) but has a higher turnover rate (ATP hydrolysis 70 s -1 ) compared to SERCA2b (K0.5 = 0.508 µM; 35 s -1 ) [38]. Diversity of SERCA isoforms in the same cell suggests that each of them could be responsible for controlling unique cell functions.…”
Section: Calcium Handling By the Sarco/endoplasmic Reticulum's Calciumentioning
confidence: 99%
“…SERCA2b differs from SERCA2a by an extension of 46 amino acids that forms an additional trans-membrane domain setting the SERCA2b C terminus in the SR lumen [37]. Functional characterization of SERCA2 isoforms performed in transfected HEK-298 cells clearly indicated that the SERCA2a isoform displays a lower affinity for Ca 2+ (K0.5 = 0.985 µM) but has a higher turnover rate (ATP hydrolysis 70 s -1 ) compared to SERCA2b (K0.5 = 0.508 µM; 35 s -1 ) [38]. Diversity of SERCA isoforms in the same cell suggests that each of them could be responsible for controlling unique cell functions.…”
Section: Calcium Handling By the Sarco/endoplasmic Reticulum's Calciumentioning
confidence: 99%
“…The ATP2A2 gene encoding the SERCA2 protein is alternatively spliced and processed in a tissue-specific manner, giving rise to three isoforms: SERCA2a, which is expressed predominantly in cardiac/slow-twitch skeletal muscle; SERCA2b, which is expressed ubiquitously; and SERCA2c, which has been reported to have a broader expression pattern than that typically attributed to SERCA2a. The level of SERCA2c protein relative to coexpressed SERCA2a or SERCA2b is not known (13,19,35). SERCA2b has a higher apparent affinity for Ca 2ϩ and turns over at a rate twofold slower than SERCA2a.…”
mentioning
confidence: 99%
“…SERCA2c has a lower apparent Ca 2ϩ affinity and a slower turnover rate than SERCA2a. The functional differences are due to replacement of the COOH-terminal sequence AILE (amino acids 994 -997) in SERCA2a, by a 49-to 50-amino acid hydrophobic tail in SERCA2b (32,34), and by the 6 amino acids (i.e., VLSSEL) in SERCA2c (13). SERCA1 and SERCA2a are subject to regulation by phospholamban and sarcolipin, which modulate their activity by decreasing their apparent affinity for Ca 2ϩ (36), so that the values for this parameter determined in the recombinant system do not match those observed in the endogenous setting.…”
mentioning
confidence: 99%
“…SERCA1 is expressed in fast-twitch skeletal muscle (26). SERCA2-ATPases exist in three different isoforms: SERCA2a and SERCA2c are the Ca 2ϩ -ATPases of cardiac and slowtwitch skeletal muscle (13,21), whereas SERCA2b is expressed in all tissues including heart and smooth muscle (17). SERCA3 can be found in different nonmuscle tissues as vascular and tracheal epithelium and pancreatic ␤-cells (1,2).…”
mentioning
confidence: 99%